HYDROGEN LOSS FROM OLIVINES IN MANTLE XENOLITHS FROM SIMCOE (USA) AND MEXICO: MAFIC ALKALIC MAGMA ASCENT RATES AND WATER BUDGET OF THE SUB-CONTINENTAL LITHOSPHERE - Peslier A.H.; Luhr J.F. (My University, 2006)
Olivines in spinel-peridotite mantle xenoliths from Simcoe (Washington State, USA) and Mexico were analyzed by Fourier-transform infrared spectrometry (FTIR) to determine their water contents. The main OH absorbance peaks of most samples are located between 3600 and 3450 cm-1 (Group I), with a few samples having minor peaks between 3450 and 3100 cm-1 (Group II). Olivines from one Mexican sample have larger peaks in Group II than in Group I. Most of these OH peaks are predicted by experimental data from the literature in the appropriate range of silica activities and iron contents. A few high-forsterite olivines, however, have mainly Group I peaks which at these low iron contents is characteristic of low-silica activity. Because these olivines coexist with orthopyroxene in the peridotite, buffering silica activity at relatively high values, their FTIR spectra may reflect disturbance of their hydrogen by melts or fluids, most probably associated with the host magma. In eight out of nine samples for which measurement at the olivine edges was possible, water contents are higher in the grain centers than at their edges, with cross-sections showing typical diffusion profiles. Moreover, water concentrations in some samples increase with olivine size. Loss of hydrogen from the olivine during xenolith transport to the surface is likely responsible for these variations. These water-concentration gradients allowed calculation of the duration of hydrogen loss, which ranges from 18 to 65 h, corresponding to host mafic-alkalic magma ascent rates of 0.2-0.5 m s-1. The highest measured water contents in olivines from individual xenoliths range from 0 to 6.8 ppm and increase with those of clino- and orthopyroxenes. Differences in hydrogen partition coefficients between olivine and pyroxenes from our data and from experiments suggest that the analyzed olivines lost at least 40% of their water during ascent from the mantle. Olivine water contents do not correlate with partial melting indices, but samples with high olivine water contents generally have low clinopyroxene La/Yb ratios and low spinel Fe3+/ΣFe ratios and resultant oxygen fugacities, and vice-versa. Metasomatism by fluids or melts and the ambient oxygen fugacity of the mantle may have played roles in the original incorporation of hydrogen into these olivines, but such primary signals have probably been obscured by later hydrogen loss. The systematically lower water contents of olivines in Mexican and Simcoe xenoliths relative to those from cratonic xenoliths may mainly reflect lower host-magma ascent velocities for mafic alkalic magmas compared to kimberlites. Calculated whole-rock water contents for the studied spinel-peridotite xenoliths range from 2.5 to 154 ppm. If 150 ppm were representative of the water content in the entire upper mantle (to 410 km), the amount of water stored there can be speculated to be only about 0.06 times the equivalent mass of Earth's oceans. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONTINENTAL UPPER-MANTLE; HOST-MAGMA ASCENT RATE; HYDROGEN LOSS; OLIVINE; WATER; XENOLITH